Advancing Ethics in Public Organizations: The Impact of an Ethics Program on Employees’ Perceptions and Behaviors in a Regional Council - Beeri, Itai; Dayan, Rachel; Vigoda-Gadot, Eran; Werner, Simcha B. (2013)
Ethics in public administration has been a subject of growing interest for both researchers and practitioners interested in the future of governance. This study examined the relationship between ethics and performance in local governance. We tested the effects over time of an ethics program on employees’ perceptions (awareness of the code of ethics, ethical leadership, inclusion of employees in ethical decision making [EDM], ethical climate [EC], organizational commitment, and quality of work life [QWL]) and behavior (organizational citizenship behavior) in one Israeli regional council. We conducted a longitudinal study of 108 employees, using data from a two-phase survey (before implementation of the ethics program and a year after) and objective assessments of employees’ behavior through managers’ evaluations. The main findings show that the ethics program was very effective, resulting in greater awareness of the code of ethics, increased inclusion of employees in EDM, and an improved EC. Furthermore, ethical leadership was positively related to employees’ awareness of the code of ethics, increased inclusion of employees in EDM, an improvement in the EC, greater organizational commitment, and higher QWL. Implications and suggestions for future studies are discussed.
Keywords: Local Government; Organizational Citizenship Behavior; Quality of work life; Organizational Commitment; Ethical Climate; Ethical decision making; Ethical Leadership; codes of ethics; Ethics program; Public organizations